Republic of Lithuania : Staff Report for the 2000 Article IV Consultation and First Review Under the Stand-By Arrangement. (IMF Staff Country Reports; Country Report, 2001)
Lithuania showed good economic growth and low inflation, under the Stand-By Arrangement. Executive Directors commended the fiscal adjustment and structural reforms. However, domestic demand remained weak and unemployment continued to rise. Directors appreciated the sound financial system and the banking supervision. They emphasized the need to maintain fiscal and monetary policies. They agreed that the privatization of the state-owned banks will foster competition in the banking sector and promote sustainable credit growth to the private sector.